A Control Algorithm of Active Wave Compensation System Based on the Stewart Platform - Wu, Huiyuan; Yang, Wenlin; Ong, Muk Chen; Fan, Tianhui; Yin, Guang; Zeng, Weixiang; Situa, Weilun; Wang, Yunting (Journal of physics. Conference series, 2023)
Aim at the actual engineering requirements of wind power operation and maintenance under complex sea conditions, a control method of the active wave compensation system for maintenance ships based on the Stewart platform is presented. The kinematics of the platform is analyzed, and the coordinate transformation, pose, and inverse solutions are analyzed and calculated. The multi-body dynamics simulation model is established by using MATLAB. For the problem of the load nonlinearity and strong coupling of the nonlinear Stewart platform, an active wave compensation active disturbance rejection control (ADRC) is built to attain the high-precision control of the six-degree-of-freedom (6-DOF) Stewart platform. The numerical simulation shows that the proposed control scheme has good tracking accuracy and strong anti-interference ability.